فلسفہء قرآنی میں تدبر وعمل کے پہلو: ایک تحقیقی جائزہ - Syed Ghazanfar Ahmad; Shaista Wahid (Pakistan Journal of Islamic Research)
The Qurʼān is an ocean of knowledge and wisdom which envisions everything sphere of life. Its thought-provoking aspects build deep insight, illuminate hearts with the divine radiant light, and guide everyone towards the righteous track, leading to eternal success.  If one wants to feel the pleasure of talking to Allah, read the word of Allah with an open heart~ the Qurʼān, an incomparable extraordinary Book. It led the companions of the Prophet (peace be upon him) from ignorance to leadership. It melted their hearts, eyes brimmed with tears, and purified their soul. Do we still choose to be distant from it? The miraculous effects of the Qurʼān are still evident as they were fourteen hundred years ago. Still as applicable as it was to the Prophet (SAW) and his Companions. The gap between the Qurʼān and Muslims is because they are ignorant of the hidden gem in their hands. They are unaware of the precious pearls they hold. Allah has given an open invitation to every sane individual to ponder over the thought-provoking verses. Studying in depth is essential for the correct implementation and our salvation lies in it. When Allah addresses through this Book, the hearts of those who read and listen to it carefully, transform for the better. Scholars are sincerely trying to educate the people in this regard so that the Muslim Ummah can genuinely benefit from this Divine book. The purpose of this article is to draw attention to the root cause of the decline in the character of Muslims and to consider effective strategies by which the practical implementation of the Qurʼān is possible. This is the way to restore the status of an ideal Muslim model of high morals and character for the entire world and emerge as a strong Muslim Ummah.